Gender Differences in the Academic Performance of Students - Parajuli, Mankumari; Thapa, Ajay (Journal of Development and Social Engineering, 2017)
This study aimed to examine gender differences in the academic performance of students. The data were collected from 240 students who passed the district level standard exam of grade eight in 2016 and were studying in grade nine in public and private schools in Lekhnath Municipality, Kaski, Nepal. The data on the characteristics of students, their parents, students’ behavior, perceptions, family environment, school environment were collected from the students, and their parents, and teachers using a structured questionnaire. The data on student’s results and divisions scored by students as measures of academic performance of the students were obtained from the District Education Office (DEO) of Kaski. The study found significant gender differences in the academic performance of students. The female students were found outperforming their male counterparts. The study also revealed that a large majority of the students scored first division or higher with relatively an outstanding performance by private schools compared to public schools. The students of private schools seem to perform better in task completion, attendance and assertiveness as well.